Kajian Awal Pemanenan Siput Laut (Gastropoda) di Pantai Krakal, Yogyakarta III: Aktivitas Wisatawan - Santi Ari Andi; Felicia Zahida; B. Boy Sidharta (Universitas Atma Jaya Yogyakarta, 2005)
This study wanted to elucidate the role of tourists activities to the beach such as Krakal Beach, Yogyakarta. The method used in this research was direct interview to the visitors using accidental sampling with the help of prepared questionnaire. This study showed that 86% visitors were in their school age. Person in this age like such a challenge like what they met during beach visit. Those make the visitation frequency quite high by repeating their visit (53,5%). Shells and shells handicrafts has been proven to be the reason why visitors come back to visit the beach (79%). Apparently, visitors agree that the snails’ forms and colors are attactive (70,9%), beautiful and unique (75,6%), but only 14% said that it shouldn’t be disturb by human activities. Their attractiveness to the snails did not make them to collect intentionally, enough for them to see and let them go (66,2%). They did not agree that visitors collected them (51,2%), but they agree harvesters make a souvenirs and get an income from this activity (67,4%). In short, they were much environment friendly (57%) rather than economic friendly (43%).